2014
DOI: 10.1111/jace.13206
|View full text |Cite
|
Sign up to set email alerts
|

High‐Temperature Creep Behavior ofSiOCGlass‐Ceramics: Influence of Network Carbon Versus Segregated Carbon

Abstract: Three silicon oxycarbide samples with different carbon contents are analyzed in the present study with respect to their hightemperature creep behavior. The tests were performed in compression at 1100°C, 1200°C, and 1300°C; in this temperature range the mechanism of creep relies on viscoelastic flow within the samples and has been modeled with the Jeffreys viscoelastic model. After the release of the applied mechanical stress, a viscoelastic recovery behavior was observed in all samples. The creep behavior of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
37
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(44 citation statements)
references
References 26 publications
7
37
0
Order By: Relevance
“…Papendorf et al [50] and Ionescu et al [51] have recently studied the compression creep behaviour at high temperatures (i.e. 1100-1300°C) of dense silicon oxycarbide-based ceramics obtained by the PDC route.…”
Section: Analysis Of Induced Creep Mechanisms Based On Tem Observationsmentioning
confidence: 99%
“…Papendorf et al [50] and Ionescu et al [51] have recently studied the compression creep behaviour at high temperatures (i.e. 1100-1300°C) of dense silicon oxycarbide-based ceramics obtained by the PDC route.…”
Section: Analysis Of Induced Creep Mechanisms Based On Tem Observationsmentioning
confidence: 99%
“…For the PDC route, specific rheological investigations are limited to a few PCP systems . Even less frequent are rheological studies with direct correlations to common shaping processes, such as extrusion or melt spinning .…”
Section: Conventional and Pdc‐based Tape Casting Comparedmentioning
confidence: 99%
“…109 For the PDC route, specific rheological investigations are limited to a few PCP systems. 56,[110][111][112][113] Even less frequent are rheological studies with direct correlations to common shaping processes, such as extrusion or melt spinning. 114 To the best of our knowledge, no specific investigation on mechanical properties of cross-linked PCPs before pyrolysis was performed so far.…”
Section: Based Tape Casting Comparedmentioning
confidence: 99%
See 1 more Smart Citation
“…The viscous silica continuous phase and the elastic carbon network have different influence on the activation energy. Ionescu et al 37) found that the carbon network decreases the activation energy and that at higher temperatures the viscous silica phase dominates the creep behaviour. The activation energy for the SiOC/MoSi 2 -composites was higher; 206 and 220 kJ/mol for 17 and 30 vol.-percent MoSi 2 , respectively.…”
Section: Thermal Expansion Coefficient and Creep Behaviourmentioning
confidence: 99%